Delayed ocular disengagement from arousing scenes - De Cesarei, Andrea; Sambuco, Nicola; D’Ascenzo, Stefania; Nicoletti, Roberto; Codispoti, Maurizio (Frontiers in Psychology, 2023)
Visual exploration of the world is supported by eye movements which can be speeded up or delayed depending on bottom-up stimulation, top-down goals, and prior associations. Previous studies observed faster initiation of saccades toward emotional than neutral natural scenes; however, less is known concerning saccades which originate from emotional, compared with neutral, scenes. Here, we addressed this issue by examining a task in which participants continuously moved their gaze from and towards pictures (natural scenes), which could be emotional or neutral, and changed position in every trial. Saccades were initiated later when the starting picture was emotional compared to neutral, and this slowing was linearly associated with the arousal value of the picture, suggesting that ocular disengagement does not vary with stimulus valence but is affected by engaging picture contents such as erotica and threat/injuries.